2017
DOI: 10.7196/samj.2017.v107i11.12805
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learnt from the introduction of the contraceptive implant in South Africa

Abstract: In 2014, South Africa (SA) introduced the subdermal contraceptive implant with the aim of expanding the contraceptive method mix and availability of long-acting reversible methods in the public sector. Three years on, concerns have been raised about the decline in uptake, early implant removals and challenges in service delivery. This article explores the lessons learnt from the introduction of contraceptive technologies elsewhere and applies these to the SA context. Drawing on the World Health Organization’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 25 publications
6
49
0
1
Order By: Relevance
“…In 2017, Pleaner et al documented challenges with rolling out the contraceptive implant in South Africa [36]. Challenges noted by the authors were observed in this study.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In 2017, Pleaner et al documented challenges with rolling out the contraceptive implant in South Africa [36]. Challenges noted by the authors were observed in this study.…”
Section: Discussionsupporting
confidence: 48%
“…In fact, 'demand creation' was thought to be one of the biggest national challenges with regard to scaling up contraceptive provision. Speaking to this observation for the implant in particular, Pleaner et al (2017) stressed the importance of managing healthcare providers' expectations of demand over timeincluding the "boom bust" phenomenon observed when a new method is introduced and then interest wains [36].…”
Section: Discussionmentioning
confidence: 99%
“…[9] Problems with new methods, if not corrected, often lead to withdrawal of methods from national programmes. [10] The World Health Organization (WHO) framework for the introduction of new contraceptive methods suggests a three-stage process, which starts with determining a need for the new method according to end-user needs (Stage 1), conducting service delivery and end-user research (Stage 2), and exploring implications of research for utilisation of the method (Stage 3). [9] As per Stage 1, the DoH introduced the implant, recognising the need for an expanded method mix and methods that were not user dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties with new methods, when left unaddressed, often lead to their discontinuation. [24] Moreover, the possibility that depot medroxyprogesterone acetate will be withdrawn from the method mix owing to its association with HIV acquisition, provides a particularly compelling reason for shoring up the performance of implant provision.…”
Section: Resultsmentioning
confidence: 99%
“…[24] An article by Pillay et al, [5] published in this edition of SAMJ, examines the data-monitoring systems used in facilities, noting considerable gaps. A range of tools were being used to record insertions, while data were seldom captured on removals, and pharmacovigilance data not at all.…”
Section: Guest Editorialmentioning
confidence: 99%